UTILIZATION OF MOODLE LEARNING MANAGEMENT SYSTEM (LMS) BY UNDERGRADUATE STUDENTS AT THE KINGS UNIVERSITY COLLEGE, GHANA - Prof. Kalyan Kumar Sahoo, Dr. Jonathan Odame, Dr.Abbul Hasan Khan (International Journal of Advanced Science and Technology, 2020)
Today, university students have become so much inclined with technology with a majority of them having personal computers at their disposal. In sub-Saharan Africa and Ghana particularly, emerging evidence has suggested a broad range of circumstances surrounding the use of a learning management system in improving teaching and learning. The purpose of the study was to examine how effectively the learning management system is being utilized by Ghanaian university students, particularly at Kings University College, Accra. The survey research design was used for the study. Using questionnaires, data were collected from 178 undergraduate students in finding out their awareness, challenges and future use of the MOODLE LMS. The analysis of data revealed the channel of awareness of the MOODLE LMS was very low (M=1.34, SD=0.44). Again, the students were experiencing challenges such as poor internet connectivity, lack of computer skills among others when using the platform (M = 4.55, SD = 2.15). In spite of this, they were willing to use the MOODLE LMS in future for their academic work (M=4.42, SD=2.20). The outcome of the data analysis perhaps suggests that acquiring adequate technology infrastructure, organizing seminars and asking students to use the LMS may not enough. Furthermore, effective utilization of the LMS should be based on mandatory institutional policies and objectives. The study contributes to the discourse on the integration of the LMS from the perspective of undergraduate students studying in a Ghanaian private university. Based on the findings, the study recommends effective computer training for students as it will go a long way in making the e-learning platform friendlier to use.